Handbook of research on e-government readiness for information and service exchange : utilizing progressive information communication technologies - Rahman, Hakikur, 1957- (Hershey, PA : Information Science Reference, 2010)
Formulates ICT strategies and critical comprehensive research for the development of efficient and effective e-government systems. This collection provides knowledge to researchers and academicians with an analysis of diversified approaches and patterns.
Citizen engagement and participation Content management solutions Developing electronic public services Development of e-government action plan E-business policies and strategies E-government services and management Identity management solutions Interoperability frameworks Mobile and ubiquitous services Open source for electronic government Security and privacy infrastructures Semantic Web applications
Includes bibliographical references and index.
Keywords: Internet in public administration; Public administration -- Information technology; Communication in public administration -- Technological innovations; Exchange of government information